Usefulness of the Ultrasound in Hand Surgery: Part I - Díaz, Homid Fahandezh-Saddi; Fernández, Fernando Dávila; Horcajadas, Ángel Bueno; Martínez, Manuel Villanueva; Yubero, María Elena Cantero (Revista Iberoamericana de Cirugía de la Mano, 2021)
In the last years, ultrasonography (US) of the wrist and hand have increased in popularity. Technical advances led us to improve image quality and have the ability to see superficial soft-tissue structures with high resolution with the patient in our office.The advantages of US are the fact that it is noninvasive, its lack of ionising radiation, low cost, and portability. The dynamic real-time assessment in the office is an additional benefit.Ultrasound can be used in hand surgery for both diagnostic and therapeutic purposes. We can use US for injections with needle guidance, for the evaluation of soft-tissue masses, foreign bodies, tendon injuries, compressive neuropathies, and rheumatologic joint disease. It also helps us perform ultrasound-guided procedures: carpal tunnel syndrome, trigger finger, and intersection syndrome or compartimental syndrome.The aim of the present review is to describe different uses of US in hand surgery to show its important role of providing to the surgeon more information on the diseases of their patients.
Keywords: hand; ultrasound-guided procedures